Examining empirical model of servant leadership, collectivism, power distance, communicative Budi context and team effectiveness: Materializing Malay contextual culture in Malaysian workplace - Abu Bakar, Hassan; Mustaffa, Che Su; Halim, Haslina; Omar, Nuredayu; Ramli, Romlah (Universiti Utara Malaysia, 2013)
The aim of the present study is to assess the communication and cultural context constructs through the development and validation of communication measures for the Malaysian workplace.The item analysis involved 200 state development employees, followed by the construct and criterion-related validation using 590 employees, representing three organizations in Malaysia, resulting in the development of communication and cultural context scales for the Malaysian workplace.The results provided support on the use of language (pekerti) and communication and interaction (bicara), which are identified from the items generation procedure.This study also develops a multi-level model to advance research on how the cultural context in a workplace moderates the relationship between servant leadership and team-level organizational citizenship behavior (OCB) in a collectivist workplace setting.We tested the model by using hierarchical linear modeling (HLM) with data obtained from 590 employees representing 82 workgroups in three organizations.The cross-level analysis indicated that the relationship between servant leadership at the individual level is strongly related to team-level OCB at the group level and moderated by the use of language (pekerti), communication and interaction (bicara) in a collectivist cultural context.Practical implications are also discussed.